Menggali Peran Perpustakaan Perguruan Tinggi di Zaman Digital: Systematic Literature Review - Delliana, Santi (Media Pustakawan, 2024)
This research aims to conduct an in-depth systematic literature review on the role of university libraries in the digital era. The Systematic Literature Review (SLR) method which focuses on Online Learning Theory with the SPIDER framework was used to analyze 32 articles obtained from the Elicit database. The findings show that the development of e-learning platforms significantly increases information accessibility and enriches the learning experience by providing diverse and interactive learning resources. The role of libraries as dynamic digital learning centers in the current information era is increasingly emphasized. Recommendations include the development of adequate technological infrastructure, relevant and up-to-date content, as well as training and technical support for library staff and users to increase the successful implementation of e-learning platforms in higher education. This study makes an important contribution in understanding the role of libraries in facing the challenges and opportunities of digital learning in the contemporary era. Thus, this research provides a strong foundation for further development in terms of strategies, policies and practices for using technology in university libraries to support more effective and inclusive learning in the digital era.